2020
DOI: 10.1002/iub.2378
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic and immunological alterations in human U937 monocytes in response to H1N1 infection

Abstract: We monitored changes that took place in glycolytic enzymes, the pyruvate end product of glycolysis, tumor necrosis factor α (TNFα), and toll-like receptors (TLRs) both at the transcriptional and translational levels upon direct interaction between PR8-H1N1 and the human monocytes U937 in vitro system. U937 were first treated with H1N1 infectious viral particles or phorbol-12-myristate-13-acetate (PMA) or left untreated and later infected with the H1N1 virus. Levels of phosphofructokinase 1 (PFK1) and pyruvate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…These metabolic changes are necessary for tasks leading to virus replication, a process, which in a very short time, demands a considerable amount of energy ( 78 , 79 ). Experiments on different viruses have demonstrated species- and time-related infected cells’ metabolic patterns obviously because of the different productivities when it comes to virus-type specificity or the infection dynamics reflected in the host cell type-specific metabolism ( 2 , 5 , 80 82 ). Moreover, there have been discussions on the changes in metabolic dynamics in different human and mouse immune cells on the infection with Epstein–Barr virus (EBV), flu, and human immune deficiency virus (HIV) and are reported with glycolytic activity, for example, with the metabolite phosphoenolpyruvate (PEP) activity and the intracellular redox state ( 82 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These metabolic changes are necessary for tasks leading to virus replication, a process, which in a very short time, demands a considerable amount of energy ( 78 , 79 ). Experiments on different viruses have demonstrated species- and time-related infected cells’ metabolic patterns obviously because of the different productivities when it comes to virus-type specificity or the infection dynamics reflected in the host cell type-specific metabolism ( 2 , 5 , 80 82 ). Moreover, there have been discussions on the changes in metabolic dynamics in different human and mouse immune cells on the infection with Epstein–Barr virus (EBV), flu, and human immune deficiency virus (HIV) and are reported with glycolytic activity, for example, with the metabolite phosphoenolpyruvate (PEP) activity and the intracellular redox state ( 82 ).…”
Section: Resultsmentioning
confidence: 99%
“…A clear example is a lymphocyte that can turn from a relatively static cell to another involved in growth and proliferation that produces considerable cytokine storms or effector molecules ( 3 ). Moreover, metabolic programming will also affect specific levels of metabolites that consequently result in different immune cell functionalities ( 1 , 4 , 5 ). These changes in metabolite levels include a rich and diverse set of post-translational modified forms of enzymes or products of glycolysis and tricarboxylic acid (TCA) cycle in immune cells that have not been fully understood yet ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our flux analysis indicated that some metabolic enzymes in the glycolytic pathway of PBMCs were responsible for inflammatory activation, although there was lack of reports on their inhibitors. Multiple activated glycolysis-related metabolic enzymes, such as phosphofructokinase (PFK, in HMR_4379 with differential flux of 5.31), phosphoglycerate mutase (PGAM, in HMR_4365 with differential flux of 4.65), and solute carrier (SLC) family 2 member 3 (SLC2A3) (in HMR_5029 with differential flux of 2.56), are necessary for maintaining macrophage activation [ 61 , 62 , 63 ]. Therefore, these metabolic enzymes had the potential to act as targets for reducing inflammation and treating COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…The host response and the clearance of viral infections rely generally on type I and III interferon (IFN) production [52]. Immune cells sense viral infection through identification of virus-derived pathogen-associated molecular patterns (PAMPs), such as viral RNA.…”
Section: Sars-cov-2 In Immune Cellsmentioning
confidence: 99%